(untitled) (Colombia Medica, 2010)
Introduction: The high polymorphism of the HLA system allows its typification to be used as valuable tool in establishing association to various illnesses, immune and genetic profiles; it also provides a guide to identifying compatibility among donors and receptors of organs transplants. Objective: To establish HLA-A, HLA-B, and HLA.DRB1 allele, genotype and haplotype frequencies among patients treated at Clinica Colsanitas SA. Methods: 561 patients coming from different regions in Colombia, who were attended in 8 centers of the clinical laboratory of the Clinica Colsanitas in different cities of the country from January 2004 to August 2008, were included in this study. All were HLA-A,-B, and -DRB1 typified via SSP PCR. Allele, genotype and haplotype frequencies were estimated with STATA Software Version 9.0 and the GENEPOP genetic analysis package. Results: 19, 28, and 15 different alleles were identified for loci HLA-A,-B and -DRB1, respectively. Alleles found most frequently were A*24 (26.2%), A*02 (26%), B*35(22.7%), and DRB1*04 (24%). The most frequent genotypes were A*02,24 (14.2%), B*07,35 (5.5%), DRB1*01,04, and DRB1*04,04 (6.9%); while most the frequent haplotypes were HLA A*24, B*35 (9.2%), A*24, DRB1*04 (8.1%); B*35, DRB1*04 (7.8%), A*2 DRB1*04 (7.4%). Conclusion: The results obtained provide a useful reference framework for the population studied, allowing compatibility probability calculations to be performed for organ transplants.